The Indirubin Derivative 6-Bromoindirubin-3'-Oxime Activates Proteostatic Modules, Reprograms Cellular Bioenergetic Pathways, and Exerts Antiaging Effects. - Tsakiri, E.N.; Gaboriaud-Kolar, N.; Iliaki, K.K.; Tchoumtchoua, J.; Papanagnou, E.D.; Chatzigeorgiou, S.; Tallas, K.D.; Mikros, E.; Halabalaki, M.; Skaltsounis, A.L.; Trougakos, I.P. (Antioxidants & Redox Signaling, 2017)
Organismal aging can be delayed by mutations that either activate stress responses or reduce the nutrient-sensing pathway signaling; thus, by using Drosophila melanogaster as an in vivo experimental screening platform, we searched for compounds that modulate these pathways. We noted that oral administration of the glycogen synthase kinase 3 (Gsk-3) inhibitor 6-bromoindirubin-3'-oxime (6BIO) in Drosophila flies extended healthy life span. 6BIO is not metabolized in fly tissues, modulated bioenergetic pathways, decreased lipid and glucose tissue load, activated antioxidant and proteostatic modules, and enhanced resistance to stressors. Mechanistically, we found that the effects on the stress-responsive pathways were largely dependent on the activity of the transcription factor nuclear factor erythroid 2-related factor (Nrf-2). Genetic inhibition of Gsk-3 largely phenocopied the 6BIO-mediated effects, while high levels of Gsk-3 expression and/or kinase activity suppressed proteostatic modules and reduced flies' longevity; these effects were partially rescued by 6BIO. Also, 6BIO was found to partially reduce the 3-phosphoinositide-dependent protein kinase-1 (Pdpk1) activity, a major effector of the insulin/insulin-like growth factor-1 cell signaling pathways. 6BIO exerts the unique property of increasing stress tolerance and in parallel partially suppressing the nutrient-sensing pathway signaling. Our findings suggest that the 6BIO scaffold can be used for the development of novel antiaging compounds. Antioxid. Redox Signal. 27, 1027-1047.